2011
DOI: 10.1002/cncr.26661
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor and insulinlike growth factor 1 receptor expression predict poor survival in pancreatic ductal adenocarcinoma

Abstract: BACKGROUND: The aim of this study was to evaluate the expression of epidermal growth factor receptor (EGFR) and insulinlike growth factor 1 receptor (IGF‐1R) proteins and IGF‐1R gene copy numbers in pancreatic ductal adenocarcinoma in relation to patients' characteristics and prognosis. METHODS: Immunohistochemical staining was performed on formalin‐fixed paraffin‐embedded tissue derived from tumor specimens recovered during surgery. Slides were evaluated for membranous EGFR and IGF‐1R staining using both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 44 publications
5
75
3
Order By: Relevance
“…In a study of colorectal cancer cases with regional lymph node involvement, coexpression of the IGF-1 receptor (IGF1R) and EGFR was present in more than 75% of tumors [24]. Moreover, the EGFR and IGF1R crosstalk has been demonstrated in other cancers such as pancreatic cancer and breast cancer [25], [26], [27], [28]. Interestingly, in pancreatic cancer, cases with high membrane expression of IGF1R and cytoplasmic detection of EGFR were correlated with poor prognosis [25], [26].…”
Section: Chiefly Produced By Receptor Functionmentioning
confidence: 99%
“…In a study of colorectal cancer cases with regional lymph node involvement, coexpression of the IGF-1 receptor (IGF1R) and EGFR was present in more than 75% of tumors [24]. Moreover, the EGFR and IGF1R crosstalk has been demonstrated in other cancers such as pancreatic cancer and breast cancer [25], [26], [27], [28]. Interestingly, in pancreatic cancer, cases with high membrane expression of IGF1R and cytoplasmic detection of EGFR were correlated with poor prognosis [25], [26].…”
Section: Chiefly Produced By Receptor Functionmentioning
confidence: 99%
“…IGF-I is a well-recognized stimulator of cancer cell proliferation and potent inhibitor of apoptosis [22,23]. Expression of IGF-I receptor was detected in samples of resected pancreatic cancer and was associated with higher histological grade, tumor aggressiveness and poor prognosis [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…In PDAC patients, studies have reported on increased intratumoral expression of IGF1R (Hakam et al 2003) and this has been associated with higher tumor grade and poor survival (Valsecchi et al 2012). Furthermore, increased amounts of IGF1 and IGF-binding proteins have been detected in sera and tissues of PDAC patients (Korc 1998, Karna et al 2002.…”
Section: The Igf System In Pdacmentioning
confidence: 99%
“…IR and IGFR belong to the same family as EGFR and trigger similar cascades. Analysis of human PDAC samples showed existence of a potential cross talk of IGF1R with EGFR that may be relevant for progression and metastasis of cancer and to predict patient outcome (Ueda et al 2006, Valsecchi et al 2012. In this regard, the cellular localization of both receptors seems to be important, as especially the membrane-dominant IGF1R and the cytoplasmic-dominant EGFR expression was related to poor survival and higher tumor grade (Ueda et al 2006).…”
Section: How Do Igf and The Insulin Systems Cooperate And Collaboratementioning
confidence: 99%